Type 2 diabetes mellitus and hearing impairment as seen in a tertiary hospital in Port Harcourt - Uju, Ibekwe Matilda; Simeon, Afolabi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Diabetes mellitus prevalence has been on the increase especially the type 2. This study therefore is to determine the pattern, type and severity of hearing impairment and correlating it with the duration, presence of peripheral neuropathy, glycaemic control of the type 2 diabetes mellitus seen in university of Port Harcourt teaching hospital (UPTH). Methods: It is a descriptive cross sectional study of adult diabetic patients seen at the endocrinology clinic of University of Port Harcourt teaching hospital. Consecutive patients with confirmed diagnosis of diabetes mellitus that gave their informed consent were recruited. A semi structured questionnaire aimed at obtaining the biodata, duration of diabetes and level of control, presence of neuropathy was administered to these patients. They had otoscopy done in addition to audiometric evaluation using pure tone audiometry. Results: The study involved 108 subjects with confirmed diagnosis of type 2 diabetes mellitus. Males; 42 and females; 66. Age ranged from 20 -81years. Hearing impairment was present in 68.52% of the subjects. Audiometric pattern showed 54.6% with SNHL while 31.5% had normal hearing. Majority of the subjects had mild degree hearing loss (50%). Bilateral SNHL was the commonly seen type of hearing loss in 55.93%. Conclusions: There is a high prevalence of hearing loss in patients with type 2 diabetes mellitus. The commonest type of hearing loss in these subjects was bilateral mild sensorineural hearing loss. There is therefore a need to incorporate regular audiologic assessment in the management protocol of the adult diabetic patients.